EVALUASI UNJUK KERJA ALAT PENUKAR KALOR JENIS CONCENTRIC DENGAN VARIASI KECEPATAN ALIRAN FLUIDA KERJA - Nugraha, Andra; Asnawi, A (Malikussaleh Journal of Mechanical Science and Technology, 2023)
Heat transfer is a science of heat transfer energy that is indispensable for analyzing the heat transfer process. One type of heat exchanger that is widely used is the Concentric heat exchanger. From the explanation of the theory that the influence of increasing the flow velocity of the cold fluid will affect the increase in the value of the performance of the heat exchanger.  Therefore, this influence will provide an increase in heat transfer performance, especially at the heat transfer rate, (Q), heat transfer coefficient (U), and also heat transfer effectiveness (Îµ). By increasing the variation in the flow velocity of cold fluid by setting the temperature of the hot fluid (Thi) at 45°C and the temperature of the cold fluid (Tci) at 27°C and also made constant up to the highest velocity variation in the cold fluid. From the most minimum performance value at a cold fluid flow rate of 0.067 m/s to 0.134 m/s  in the concentric heat exchanger type, performance values were obtained including the heat transfer rate (Q) from 714.09 Watts to 1111.51 Watts on the heat side and 619.89 Watts to 901.83 Watts on the cold side, for the heat transfer coefficient (U) a value of 337.90 W / m2 was obtained. C to 405.38 W/m2. C , and for the effectiveness (Îµ) which was originally 29% to 43%.